The appreciation of artistic aspects of the Code of Points in rhythmic gymnastics: an analysis of the last three decades - Eliana de TOLEDO; Kizzy ANTUALPA (Escola de Educação Física e Esporte da Universidade de São Paulo (EEFEUSP), 2016)
Abstract In pursuit of promoting the artistic aspects, the current Rhythmic Gymnastics Code of Points (RGCP) has been submeted significant changes that motivated this research, documentary and historical in character, which aimed to analyze the last eight Olympic cycles of RGCP. The research method used in this study is documentary and characterized by the information found in documents (RGCP) that had not received any scientific treatment. From the analysis of different RGCP cycles, we found artistic aspects, and their connection with RG technical requirements. We observed that the RG has distinct stages (technical aspects, flexibility etc). While retaining its artistic roots (from Dance and Rhythm), in pursuit of sportivization and systematization of the sport, the first stage was characterized by a search for the sportivization and standardization of the modality based on the inclusion of new body elements in the RGCP . The second stage confirms our previous hypothesis, that in the last RGCP the artistic component had undergone few changes. We noticed, in an overview, that at the present time the current RGCP brings back the relationship between RG and its origins, influenced by Aesthetic Gymnastics (Swedish), Rhythmic and Dance. Condition observed once the current Code of Points (2013-2016) marks the story of sports, by two aspects: the permissiveness of routines with singing wich has not allowed since since the creation the RGCP and significant changes to the appreciation of the routines' artistic aspects.